2016
DOI: 10.1080/17470218.2015.1054847
|View full text |Cite
|
Sign up to set email alerts
|

Inflected words in production: Evidence for a morphologically rich lexicon

Abstract: Current evidence suggests that there is a difference between the representations of multimorphemic words in production and perception. In perception, it is widely believed that both whole-word and root representations exist, while in production there is little evidence for whole-word representations. The present investigation demonstrates that whole-word and root frequency independently predict the duration of words suffixed with -ing, -ed, and -s, which reveals that both root and word representations play a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 104 publications
(172 reference statements)
3
19
2
Order By: Relevance
“…We found a weak negative correlation between raw sign frequency and sign duration (as determined by sign onset and offset, see above), indicating that more frequent signs are shorter ( r s = −.25; p < .001). This trend is consistent with work on spoken languages showing that word frequency is inversely related to phonetic duration, though the correlation in spoken language is generally weaker (Bell et al, 2003; Caselli, Caselli & Cohen-Goldberg, 2015; Cohen-Goldberg, 2015; Gahl et al, 2012). …”
Section: Resultssupporting
confidence: 88%
“…We found a weak negative correlation between raw sign frequency and sign duration (as determined by sign onset and offset, see above), indicating that more frequent signs are shorter ( r s = −.25; p < .001). This trend is consistent with work on spoken languages showing that word frequency is inversely related to phonetic duration, though the correlation in spoken language is generally weaker (Bell et al, 2003; Caselli, Caselli & Cohen-Goldberg, 2015; Cohen-Goldberg, 2015; Gahl et al, 2012). …”
Section: Resultssupporting
confidence: 88%
“…Contrary to Caselli et al (2015), the present analyses do not distinguish between monomorphemic and morphologically complex neighbors. They also do not consider the role of neighbor orthographic similarity, which, as a reviewer points out, is an additional factor that could be at play.…”
contrasting
confidence: 98%
“…As noted above, however, Caselli et al (2015) found that lexical-phonetic effects on whole-word duration were also influenced by the number of neighbors differing in the initial consonant: Caselli et al found shortening of overall word duration (as did Gahl et al, 2012, in the same corpus), whereas here, we find lengthening of initial consonant duration. An important question for future research concerns the direction of these durational effects.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations